ANALISIS PENGARUH SISA ANGGARAN, PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL DI KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2013-2017 - Noor Aini Arifah; Haryanto Haryanto (Diponegoro Journal of Accounting, 2019)
The budget process has two components, one of which is capital expenditure in local governments by producing financial plans. The allocation of capital expenditure is based on regional needs for infrastructure and infrastructure, both for the smooth implementation of government duties and for public facilities.The purpose of this study is to examine the development budget, regional budgets and balancing funds towards the capital expenditure budget in districts / cities in Central Java Province. The sample used was 35 districts / cities in Central Java Province using data available on the internet and from the LHKPD. The results of the study show variable expenditure for the budget, regional original income, and significant balance of funds towards capital expenditure.